Inflammation, Infectious Triggers, and Parkinson's Disease - Caggiu, Elisa; Arru, Giannina; Hosseini, Sepideh; Niegowska, Magdalena; Sechi, GianPietro; Zarbo, Ignazio Roberto; Sechi, Leonardo A. (Frontiers in Neurology, 2019)
Parkinson's disease is a neurodegenerative disorder characterized by progressive loss of dopaminergic neurons of the substantia nigra pars compacta with a reduction of dopamine concentration in the striatum. The complex interaction between genetic and environmental factors seems to play a role in determining susceptibility to PD and may explain the heterogeneity observed in clinical presentations. The exact etiology is not yet clear, but different possible causes have been identified. Inflammation has been increasingly studied as part of the pathophysiology of neurodegenerative diseases, corroborating the hypothesis that the immune system may be the nexus between environmental and genetic factors, and the abnormal immune function can lead to disease. In this review we report the different aspects of inflammation and immune system in Parkinson's disease, with particular interest in the possible role played by immune dysfunctions in PD, with focus on autoimmunity and processes involving infectious agents as a trigger and alpha-synuclein protein (α-syn).